Graphene-based nanomaterial for the removal of sulfamethoxazole in water. (2020) - Masri, Aina Khalina; Yen, Tong Wei; Ahmad, Mohamad Ali; Karim, Sabrina
Abstract: As a promising nanomaterial, graphene-oxide (GO) has shown great sorption potential for environmental contaminants. The study focusing on ability of graphene oxide as adsorbent in diminishing the concentrations of sulfamethoxazole (SMX) in synthetic wastewater. This study evaluated the ability of GO to remove SMX under different dosage of GO and different initial concentration of SMX. GO was synthesized from the oxidation of graphite flakes by using Optimized Improved Hummer's method while the sorption study was done using the batch experiment. The result indicates that GO was able to removed up to 14.40% of SMX by optimizing the dosages of GO from 0.02 g to 0.1 g. Under different initial concentration of SMX, from 5 mg/L to 20 mg/L, the ability of GO to remove SMX is up to 5.20%. Both experimental system fit with Langmuir Isotherm Model. This indicated GO has the ability to removed SMX in higher concentration however the reaction time need to be increase. Results obtained from this work demonstrated that GO can be used as an effective adsorbents for the removal of antibiotic.